KINERJA BADAN PENANGGULANGAN BENCANA DAERAH DALAM MENANGGANI PRA BENCANA GUNUNG SLAMET DI DESA KUTABAWA KECAMATAN KARANGREJA KABUPATEN PURBALINGGA JAWA TENGAH - Andhini Amirudin Ambo; Susi Sulandari; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aimed to describe and analyze the performance of the Regional Disaster Management Agency The Purbalingga in handling pre-disaster on Mount Slamet , is already in line with the vision and mission BPBD , as well as to describe and analyze what are the dimensions that hinder the performance of BPBDs . This research was conducted through qualitative descriptive . The number of informants in this study were 3 informants Chief executive , head of administration of sub-section , and the section head of preventive and preparedness measures taken by purposive sampling technique . Data collection techniques by observation , interviews , documentation and literature study. The results showed that the dimension of productivity , responsibility , and accountability BPBD ;p[;Purbalingga in pre-disaster activities were optimal . There is still not optimal dimensions of BPBD The Purbalingga the dimensions of service quality and responsiveness. The conclusion from this study that the performance is in accordance with his vision BPBDs seen from the dimensions used productivity through socialization introduction of hazards and how to deal with it. BPBDs performance also is in conformity with its mission seen from the dimensions of productivity that are used in implementing risk reduction activities that recognize hazards and develop a culture of disaster awareness can be seen from the implementation of all pre-disaster activities in the village Kutabawa.